Development of Flashcard Learning Media with Dual QR – Code Based on Augmented Reality and Live Worksheet on Chemical Bonding Materials - Andoni, Tri; Dalimunthe, Makharany (Journal of The Indonesian Society of Integrated Chemistry, 2026)
This study aims to develop flashcard learning media with Dual QR-Code based on Augmented Reality (AR) and Live worksheet on chemical bonding material and to determine its validity, user response, and effectiveness on student learning outcomes. This research is development research (Research and Development) with a 4D model (Define, Design, Develop, Disseminate). The research subjects included three lecturers as validators, three chemistry teachers for response teachers, and 34 grade X students in a limited trial at MAN 2 Model Medan. The instruments used were validation sheets, response questionnaires, and pretest and posttest tests. The results showed that the media had a very high level of feasibility with media validation of 96% and material validation of 91%. Teacher responses were 96% (very interesting) and student responses were 78% (interesting). The effectiveness of the media was shown by an increase in learning outcomes, with an average pretest score of 42.35 to 88.97 in the posttest and an N-Gain value of 0.81 (high category). The Wilcoxon test showed a significance value of 0.000 < 0.05, indicating a significant effect of media use on learning outcomes. Thus, the developed media is valid, engaging, and effective for use in learning chemical bonds.